The Nautical Magazine for 1871 (Cambridge library collection. Nautical magazine, 1871)
The Nautical Magazine first appeared in 1832, and was published monthly well into the twenty-first century. It covers a wide range of subjects, including navigation, meteorology, technology and safety. An important resource for maritime historians, it also includes reports on military and scientific expeditions and on current affairs. The 1871 volume, beginning a 'new series' under a new editor, opens by announcing certain changes to the magazine 'to bring it more into harmony with the spirit of this advancing age … enlarging its usefulness' so as to be 'a means of adding to the honour and prosperity of England, and to the welfare of humanity at large'. Hydrography and navigation would continue to be prominent, but leisure reading would also feature. Other new departures include substantial articles analysing topics relating to a planned Shipping Bill, reports of the meetings of learned societies, and regular articles on competitive yachting and rowing